A Falcon God from the Garden of Princess Nimet Mokhtar at el-Marg - Ashmawy Ali, Aiman; Connor, Simon (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
This article explores a monumental statue of a deity that was moved together with other antiquities in 2001 from the garden of Princess Nimet Mokhtar at el-Marg to the Open-Air Museum of Tell Basta in Zagazig. The statue was allegedly found in the garden of the palace of el-Marg, 4 km north-east of ancient Heliopolis. This estate once belonged to the sister of King Fuad I and had been part of her private collection until the property was confiscated in 1954. The statue depicts a seated male falcon-headed deity, wearing a scarab on its wig. Its stylistic features and rounded proportions indicate that it dates to the Ptolemaic Period. This statue would be the only witness to monumental activity in the area of Heliopolis, several decades after the reign of Nectanebo I.